Investigasi Pengetahuan Dasar Tentang Bahaya Sampah Plastik pada Siswa Sekolah Dasar di Pulau Maitara, Maluku Utara - Bahtiar Bahtiar; Yusmar Yusuf; M. Nasir Tamalene; Mesrawaty Sabar (Jurnal Ilmiah Wahana Pendidikan, 2022)
Maitara Island is a small island with an area of ​​206 hectares, located between the islands of Tidore and Ternate islands, and to the west of the island of Halmahera in North Maluku, Indonesia. The behavior of throwing garbage in any place, especially on the shores of beaches, rivers, and ditches is a concern for the degradation of coastal ecosystems (mangrove forests, seagrasses and coral reefs). The tendency of people's behavior to throw plastic waste in any place is influenced by the low level of public knowledge about the negative impact of plastic waste. Elementary schools (SD) are one of the largest producers of plastic waste in addition to markets, shops, offices and households. Basic knowledge of elementary school students (as future generations in the region) about the negative impact of plastic waste is important to investigate. It is also important to see the extent to which elementary schools function as educational institutions that impart non-curricular knowledge that is beneficial to students. The results showed that the basic knowledge of elementary school students on the island of Maitara about the dangers of plastic waste was categorized as sufficient. Based on the assessment of individual knowledge, there are still 34.62% of students with basic knowledge about the dangers of plastic waste are categorized as lacking. Students do not have sufficient knowledge about the properties of plastic waste (score 33.33) and the dangers of microplastics (score 55.13), but have good knowledge about the impact of waste and plastic waste (macroplastic) on human health (score 76.92). Students' knowledge about the negative impact of plastic waste on damage to aquatic ecosystems and decreasing soil productivity is in the sufficient category (scores 71.15 and 58.33, respectively). Cognitive domains related to the nature of plastic waste, the negative impact of plastic waste on decreasing soil productivity, damage to aquatic ecosystems, and the dangers of microplastics still need to be developed among elementary school students on Maitara Island.